Educação e trabalho feminino: impactos sociais e econômicos da desigualdade de gênero - Ribeiro, Danielle França (2021)
Gender inequality impacts the well-being of women and society as a whole, as well as having an effect on the economic performance of countries. As it is a complex social phenomenon, it is reinforced by various events that occur throughout women's lives. Consisting of a historical and current problem, it should be the object of reflection in order to reduce the social and economic distances between men and women. Thus, this study aims to discuss, at an international level and under a gender perspective, the relations between women's education, female work and the economy of countries. For that, this dissertation consists of three articles: i) the first measures of the relationship between female child labor and dropout in basic education; ii) the second measures the impact of the female workforce on economic growth; iii) the third investigates the relationship between education and the level of female unemployment. This is an applied, descriptive and quantitative study. Secondary data from the Quality of Government Institute (QoG) based international research were used and the analysis was carried out using statistical and econometric methods. As a result, it was observed that the increase in girls in child labor is accompanied by greater school leaving, especially in countries with higher poverty rates. income transfer policies and educational investment, including school feeding programs. In addition, it was found that the determinants of economic growth per capita GDP PPP and per capita GDP growth are influenced by the participation of women in the labor market, however, it is necessary to pay attention to minimize the prejudices experienced by them in this space. Finally, it was analyzed that investment in education made by women does not necessarily lead to greater ease of entry and permanence in the labor